Banana Stem Utilization As A Plant Container With Planting Media And Watering Interval On Lettuce (Lactuca sativa L.) Productivity - Raisa Baharuddin; T. Rosmawaty; Arrusy Arrusy (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Banana pseudostem is a type of agricultural waste that has the potential to replace polybags. The planting media used in lettuce growing must be suitable for increasing plant development and productivity. Furthermore, water requirements must be met, as banana pseudostems have a high water content and are expected to minimize the watering procedure. The goal of this research was to find a good planting medium and watering interval for lettuce development and production in a banana pseudostem planting container. From March to June 2021, this study was done at UPT Agrofarm RIU. A Factorial Completely Randomized Design was employed in the study (CRD). The first is the planting medium, which is divided into four levels: M1: top soil, M2: RYP soil, M3: peat soil, and M4: RYP soil and peat soil (1:1). The second aspect is the watering interval, which is divided into three categories: F1: daily, F2: every two days, and F3: every three days. The results showed that using peat medium as a planting container and watering once every three days boosted leaf number, plant wet and dry weight, and root volume.